What she's having - Moher, Laura (Sourcebooks Casablanca, 2024)
"She may be strong, but she's not unbreakable. July Tate is a force to be reckoned with-a big, strong blond with a heart the size of her whole town--but beneath her capable exterior lie the scars of a devastating lost love. To July, love equals vulnerability, and she can't afford either. Joe Anderson knew from the first moment he saw her that July was The One. Now, after years apart, he's back, driven by the need to explain his disappearance. In search of the girl who filled his teenage dreams, he finds instead a powerhouse woman who steals his heart and soul. Joe embodies everything July has been missing, and together they spark as brightly as ever. But with Joe around, July, who can usually outwork four men is suddenly making mistakes right and left. And that scares her. Because if July falls again, this time her beloved town could go down with her. Readers of Olivia Dade, Talia Hibbert, and Lucy Score will adore this sexy Southern small town contemporary romance between a cinnamon roll hero and a plus size heroine looking for a second chance at love"--